CONSTRUCTIVISM-BASED QIRO’AH LEARNING MATERIALS WITH LECTORA INSPIRE AT MI ASSALAM LAHAT - Ade Irawan; Kristina Imron; Rendi Sabana (Universitas Islam Negeri Palopo, 2026)
This research is motivated by the gap between the potential of interactive media and the reality of qiro'ah instruction in Islamic elementary schools, which remains conventional and lacks holistic integration of constructivist approaches into digital teaching materials. The novelty of this study lies in combining the Contextual Teaching and Learning (CTL) approach grounded in constructivism with Lectora Inspire software to develop qiro'ah instructional materials for madrasah ibtidaiyah. This study aims to develop and test the effectiveness of these materials. The method used is Research and Development (R&D) adapting six stages of the Borg and Gall model, with 25 fifth-grade students of MI Assalam Lahat as the research subjects. Validation results from content experts (96%) and media experts (88%) indicated that the product was highly valid. Field trials demonstrated a significant improvement in learning outcomes, with an average N-Gain score in the medium category and very positive student responses